Selected Aspects of Cancer Progression: Metastasis, Apoptosis and Immune Response - Kaiser, Hans E.; Nasir, Aejaz (Cancer Growth and Progression, 2008)
The processes of tumor metastasis, apoptosis and anti-tumor immune response are among the most complex yet rapidly advancing fields in the area of cancer research. This monograph presents a comprehensive coverage of the recent advances in the various key concepts in these fundamental aspects of human cancer. It would be of particular interest to members of the cancer research community, especially those who are actively involved in the study of basic and translational aspects of human cancer. Specifically, this volume includes authentic subject reviews by leading experts on the following aspects: Control of tumor cell motility Role of tumor-cell adhesion and migration in organ-selective metastasis-formation Tumor heterogeneity in relation to invasion and metastasis and its clinical implications Tumor angiogenesis, angioprevention, anti-angiogenic therapies and response Role of apoptosis in the development, progression and therapy of cancer Role of macrophages in tumor development and metastasis Pathways of macrophage-mediated tumor progression Abnormal variation of immune response against cancer Immunological aspects of Marek's disease virus (MDV)-induced lymphoma progression A biodynamical model of human T-cell proliferative disorders Current methodologies for characterization of tumor directed immune response.